2021
DOI: 10.3390/biomedicines9121760
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Matrix Metalloproteinases-2 and -7 in LAM/TSC Cells

Abstract: Matrix metalloproteinase (MMP) dysregulation is implicated in several diseases, given their involvement in extracellular matrix degradation and cell motility. In lymphangioleiomyomatosis (LAM), a pulmonary rare disease, MMP-2 and MMP-9 have been detected at high levels in serum and urine. LAM cells, characterized by a mutation in the tuberous sclerosis complex (TSC)1 or TSC2, promote cystic lung destruction. The role of MMPs in invasive and destructive LAM cell capability has not yet been fully understood. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In this case, the drug treatment caused cytotoxicity, which was not observed in our experimental conditions. We previously demonstrated that 5-azacytidine treatment also reduced migratory capability and MMP2 and MMP7 secretion of LAM/TSC cells, likely because of the induction of tuberin expression [11]. Given the broad inhibitory action of 5-azacytidine on hypermethylation that leads to chromatin remodelling, as often occurs in several types of cancers, we have to consider that this drug might cause other demethylating effects besides the induction of tuberin expression, making this point a limitation of our study that could be overcome by the retroviral transduction of TSC2.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In this case, the drug treatment caused cytotoxicity, which was not observed in our experimental conditions. We previously demonstrated that 5-azacytidine treatment also reduced migratory capability and MMP2 and MMP7 secretion of LAM/TSC cells, likely because of the induction of tuberin expression [11]. Given the broad inhibitory action of 5-azacytidine on hypermethylation that leads to chromatin remodelling, as often occurs in several types of cancers, we have to consider that this drug might cause other demethylating effects besides the induction of tuberin expression, making this point a limitation of our study that could be overcome by the retroviral transduction of TSC2.…”
Section: Discussionmentioning
confidence: 96%
“…At the state of the art, this hypothesis was only proposed but not demonstrated so far [27]. Indeed, it is already known that LAM cells exploit several mechanisms to induce the remodelling of the lung parenchyma, including the secretion of molecules such as matrix metalloproteinases [11], kathepsin K [10], VEGF-D [7], IL-6 [28], and IL-8 [16], which are also SASP components released by senescent cells to modulate the behaviour of neighbouring cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paraffin-embedded tissues were sectioned (thickness of 5 μm), deparaffinized, and rehydrated in xylene and decreasing concentrations of ethanol to distilled water (100%, 95%, 90%, 80%, and 70%). Immunohistochemistry analysis was performed as previously described [ 24 ]. Briefly, slides were treated under pressure at 95 °C in citrate buffer, pH 6.0 for 5 min for antigen retrieval, and incubated with 0.3% H 2 O 2 in methanol for 20 min to quench endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%